Pemahaman Konsep Siswa Kelas XI pada Materi Struktur dan Fungsi Jaringan Hewan - Fadilla Dwi Putri; Rina Widiana; Annika Maizeli (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
This research was motivated by students' low conceptual understanding of the structure and function of animal tissues. Understanding of this concept can be seen from students' test scores on the structure and function of animal tissues. The purpose of this study was to determine students' conceptual understanding of the structure and function of animal tissues. This type of research is a qualitative descriptive research. The instrument used in this study was a reasoned multiple choice test with item analysis using the simple PAS application. Based on data analysis, it was possible to obtain students' conceptual understanding of the material structure and function of moderate animal tissue (66.6%) with categories of understanding 3.7%, 62.5% wrong concepts, and 33.7% not understanding.